2017
DOI: 10.3390/ijerph14121468
|View full text |Cite
|
Sign up to set email alerts
|

Oral Mucositis in Pediatric Patients in Treatment for Acute Lymphoblastic Leukemia

Abstract: Oral mucositis in oncologic patients is the most undesirable event of the chemotherapeutic treatment. This study aimed to identify damage to the oral cavity resulting from chemotherapy in pediatric patients with acute lymphoblastic leukemia (ALL). This is a prospective study with a sample of 42 children and adolescents evaluated for 10 consecutive weeks after diagnosis. The modified Oral Assessment Guide (OAG) was used, and data were analyzed by Spearman’s rank correlation coefficient (α = 5%). Changes to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
1
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 25 publications
0
46
1
14
Order By: Relevance
“…9 Another study with 42 patients pointed to 54.8% (n=23) female patients, with a mean age of 7.1 (± 4.7) years (median 5, minimum 2 and maximum 18 years), and distributed the patients regarding the age at diagnosis in groups of 2 (n=7; 16.7%), 4 (n=8; 19.0%) and 5 (n=4; 9.5%) years. 8 The most affected gender in the present study counteracts the literature. Regarding age, some authors are unanimous when affirming that the age at diagnosis has a strong effect over the prognosis, with more favorable outcomes for younger patients.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…9 Another study with 42 patients pointed to 54.8% (n=23) female patients, with a mean age of 7.1 (± 4.7) years (median 5, minimum 2 and maximum 18 years), and distributed the patients regarding the age at diagnosis in groups of 2 (n=7; 16.7%), 4 (n=8; 19.0%) and 5 (n=4; 9.5%) years. 8 The most affected gender in the present study counteracts the literature. Regarding age, some authors are unanimous when affirming that the age at diagnosis has a strong effect over the prognosis, with more favorable outcomes for younger patients.…”
Section: Discussioncontrasting
confidence: 56%
“…23 The most common complications are mucositis, candidiasis, periodontitis, gingivitis, ulcers, petechiae, ecchymosis, erythema, gingival bleeding, xerostomia, mucosal pallor and leukemic gingival enlargement. [7][8][9]23 However, in a prospective evaluation from diagnosis to the 10 th week of treatment, alterations in saliva and lip mucosa were observed, because of the occurrence of severe buccal mucositis throughout almost all of the evaluation weeks. 8 In the present study, only a few patients presented buccal alterations, contrasting with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in our study, the CIOM of the gingiva was not present in AML patients and was found in only one case of ALL patients. According to a recent study on oral mucositis in pediatric ALL patients, lip mucosa was the most frequently affected site, with the gingiva being a relatively uncommon site (Ribeiro, Limeira, Dias de Castro, & Ferreti Bonan, 2017). ALL is the most common and the most serious type of childhood cancer, accounting for about 80% of cases of leukemia between 0 and 19 years of age, and the prognosis for ALL is worse in adults over 30 years (Trencsenyi, Bako, Nagy, Kertai, & Banfalvi, 2015).…”
Section: Discussionmentioning
confidence: 99%